Evaluation of a broad-ranging and convenient enzyme-linked immunosorbent assay using the lysate of infected cells with five serotypes of Orientia tsutsugamushi, a causative agent of scrub typhus - Ogawa, Motohiko; Satoh, Masaaki; Saijo, Masayuki; Ando, Shuji (BMC microbiology, 2017)
Scrub typhus is a mite-borne rickettsiosis caused by infection of Orientia tsutsugamushi, which is endemic to several Asia-Pacific Rim countries, including Japan. Although micro-indirect immunofluorescent assay (micro-IFA) is the standard method for the serological diagnosis of scrub typhus, enzyme-linked immunosorbent assay (ELISA) is considered to be more objective, by providing digitized results as opposed to being subject to the judgment of the evaluator as in micro-IFA. Therefore, the aim of this study was to develop a broad-ranging ELISA using the five major prevalent serotypes of O. tsutsugamushi in Japan as the antigens. Furthermore, in contrast to previous studies that used purified microorganisms via ultracentrifugation, we directly used the infected cells, and evaluated the diagnostic accuracy of this simplified method to that of micro-IFA. Evaluation of paired patient sera against the five serotypes showed that the accuracy of ELISA relative to micro-IFA was 87.4 and 79.5% for immunoglobulin (Ig)M and IgG assays, respectively, at the optimized cut-off value. Further evaluation of patient sera against the expected serotype of the infecting strain showed that the accuracy of ELISA compared to micro-IFA increased to 100 and 97.4% in the IgM and IgG assays, respectively. This suggests that use of the five prevalent serotypes contributed to the increase of the accuracy of ELISA. When applying the criteria of serological diagnosis for paired sera samples to ELISA, all 19 patients were diagnosed as positive; a ≥4-fold elevation of the antibody titer was observed in 15 of 19 patients that were positive, and very high antibody titers were observed in both paired sera samples of the remaining four patients. In addition, all samples of healthy subjects and patients with other types of rickettsiosis were diagnosed as negative using these criteria. Our results suggest the excellent performance of the new broad-ranging and convenient ELISA, which appears to be applicable for the diagnosis of scrub typhus patients infected with the wide variety of prevalent strains in Japan. Furthermore, the ELISA is more objective than the micro-IFA, and can therefore provide more accurate diagnoses in Japan.